Personalized Intraoperative Radiotherapy Balloon Applicator Design and Production With 3D Printer - YÜZER, Öykü; ÖZER, Betül; ÖZDEL, S. Enes; GÜNAY, Osman (International Journal of Computational and Experimental Science and Engineering, 2023)
Radiation is the energy released from matter. Radiation is divided into two according to its source: natural and artificial radiation. Artificial radiation is used in treatment methods in medicine. One of these treatment methods is brachytherapy. Brachytherapy treatment is applied by placing small radioactive sources inside the body and sending beams directly to the cancerous cell. The main thing to consider in brachytherapy treatment is the selection of the applicator. The applicator is the device that enters the patient’s body cavity. In this study, based on the applicators currently used in the medical field, a patient-specific, biocompatible, sterilized, and reusable applicator will be created from PLA material by using a 3D printer. The applicator to be designed will consist of 2 parts: the intrauterine tube and the spherical tip. The spherical tips, which vary according to the size of the tumor, will be pressed to integrate with the tube part of the applicator. Thus, a patient-specific design will be realized by using the spherical tip suitable for the patient’s tumor region. As a result of the project, since the applicator will have spherical tips of different sizes, it completely covers the intrabody cavity of the patient. Thus, the movement of the applicator is limited, and dose distribution is prevented. The treatment process of the patient is improved. Another result is that the prototype applicator printed with PLA filament is produced at a very low cost. Thus, access to the applicator becomes easier and its use in the medical field increases.